Strengthening strategies of historical structures adjacent to RC buildings: A case study of the Cafer Pasha Darülkurra in Turkey - Çakır, Ferit; Kucuk, Sebahattin; Ozdemir, M. Alperen; Korkmaz, Mustafa (Elsevier Science Inc, 2023)
Rapid and unplanned urbanization is one of the biggest problems of the modern age and it occasionally leads to the destruction of historical and cultural structures. Hence, several historical structures are at risk of dis-appearing due to rapid and unplanned urbanization all around the world. Protection of historical structures, which are under the threat of unplanned urbanization, has been one of the main issues emphasized in many countries. The study focuses on the strengthening strategies of historical structures adjacent to RC buildings and develops an infographics map of strengthening strategies. In addition, a case study in which the historical Cafer Pasha Darulkurra in Kutayha Turkey, which was in danger of extinction due to unplanned urbanization, was strengthened and restored using the developed infographic map is presented. The map consists of four main steps; Levels of Information, Damage Assessment, Performance Evaluation and Restoration Works. The first step is to collect data about the main and adjacent structures such as the geometry of the buildings, details of ele-ments, characteristics of materials and relation of the main and adjacent structures. The second step is to assess the damage levels of the structures. The third step is to evaluate the performance of the structures by using finite element analyses (FEAs) and to determine the demolition plan for the adjacent structures. The last step is to carry out the strengthening and restoration of the main structures and restoration works on transferring the structure to future generations.
Keywords: Unplanned urbanization; Protection of the historical structures; Demolition of RC structures; Finite element analyses; Strengthening of the historical structures; Performance evaluation